2022
DOI: 10.2478/msp-2022-0046
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of aerosol droplets diameter generated in aerosol jet printing

Abstract: Aerosol jet printing is a contactless direct-write technique that could be used for the deposition of a variety of materials. First, used for electric paths, the technology was explored for many applications. The substantial part of the process is the generation of aerosols. The size of the droplets and the stability of the process affect the quality of the sprayed lines. This article investigates the diameter of the sprayed droplets, allowing future comparison of the results with sprayed lines. Droplets from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…It is assumed that the velocity of the discrete-phase particles is the same as that of the continuous-phase particles, and the particles are non-rotating uniform spheres. 3 The proposed CFD model does not consider the interaction between the ink and substrate. 4 The Reynolds number within the gas jetting head is Re < 2300, and the sheath gas and aerosol jet are in a laminar flow state [23].…”
Section: Experimental Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is assumed that the velocity of the discrete-phase particles is the same as that of the continuous-phase particles, and the particles are non-rotating uniform spheres. 3 The proposed CFD model does not consider the interaction between the ink and substrate. 4 The Reynolds number within the gas jetting head is Re < 2300, and the sheath gas and aerosol jet are in a laminar flow state [23].…”
Section: Experimental Methodsmentioning
confidence: 99%
“…It can also achieve conformal printing on complex surfaces. Consequently, it is widely used in microdevice fabrication, biomedical applications, and nanomaterial research [2][3][4][5][6][7], AMJP technology historical progression timeline as shown in Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…micro-and nanoscale pores within the structure, which significantly affect the properties and reliability of PFE. While in IJP the key factors contributing to the voids are usually the pinning effect, residual surface temperature, insufficient droplet overlap and surface defects [64], in AJP it is the diameter of the aerosol droplets and surface temperature [34]. What is more, the challenging issue in the AJP is the selection of parameters to avoid overspray formation.…”
Section: Introductionmentioning
confidence: 99%
“…Schematic diagram of the aerosol jet printer with an ultrasonic atomiser equipped with: A -control unit, Bmicrofluidic flow controller, C -ink reservoir, D -ultrasonic generator, E -air compressor and F -printing head with the nozzle fixed above moving bed An aerosol was generated by an ultrasonic transducer working with a frequency of 1.7 MHz and a power of 18 or 24W in a reservoir filled with 5 ml of suspension, which was conductive ink. The size of generated aerosol droplets was mostly in the range of 8-17 µm[34]. Produced aerosol was…”
mentioning
confidence: 99%